A Study on the Role of LPA and ATX in Breast Cancer in Iraq - Anfal Akeel Taha; Hind Salman Jassim; Wafaa Fadhil Hamad (Acta Medica Iranica)
Breast cancer is the most common malignancy among women and a leading cause of cancer-related mortality. Early detection is crucial for improving treatment outcomes. This study investigates the roles of lysophosphatidic acid (LPA) and autotaxin (ATX) in the early diagnosis of breast cancer among Iraqi women. A case-control study was conducted involving 75 women diagnosed with breast cancer and 75 healthy controls. Blood samples were collected, and biochemical parameters, including LPA and ATX levels, were measured using the ELISA technique. Statistical analyses were performed with SPSS version 24, and receiver operating characteristic (ROC) analysis was used to evaluate diagnostic capabilities. The majority of breast cancer patients were aged 50-59 years (33.3%). Histologically, invasive ductal carcinoma was the most prevalent subtype (82.6%). Biochemical analysis revealed significant differences in alanine aminotransferase, total serum bilirubin, and alkaline phosphatase levels between patients and controls. LPA levels were significantly elevated in the patient group (868.48±142.11 pg/ml) compared to controls (212.01±54.94 pg/ml), while ATX levels were also higher (2252.20±399.46 pg/ml vs. 951.40±209.21 pg/ml). ROC analysis indicated that both LPA and ATX exhibited high diagnostic sensitivity (98%) and specificity (100%). In Iraqi women, elevated serum levels of LPA and ATX may serve as potential diagnostic biomarkers for breast cancer, highlighting their role in disease progression. Further studies are warranted to explore their clinical applications in breast cancer diagnosis and management.